Meta-Structured Covalent Organic Framework Nanocoatings with Active and Angle-Independent Structural Coloration - Jiang, Yanqiu (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.